The current health problem: internet addiction in - Gözen, Duygu; Kurt, Ayşe Sonay; Canbulat, Nejla (Journal of Dependence, 2014)
Objective: Internet using which is the communication network of interconnected computer systems is rapidly increasing. This systematic review is planned to assess articles related with frequency and risk factors of internet addiction at childhood age and nurses’ role to prevent children from internet addiction. Method: The data were selected from articles publishing Turkish and English, to be placed in MEDLINE (PubMed), Turkish Medline and Scholar Google between January 1996 and April 2010. The terms such as “internet addiction”, “pathological internet use”, “child” and “nursing” were used in literature screening. The researches which publication language is Turkish or English, including childhood age, internet addiction, risk factors or nursing roles for prevention from internet addiction were included in the study. Results: According to the screening results; 33 researches were found as the answers of these questions. While the results of the study were analyzed, internet addiction rate was determined to vary between 2.4 to 60 %. Risk factors which can be caused to internet addiction were age (adolescent), sex (male), psychological problems, using internet at home, purpose of using internet (games, chat), connecting to the internet duration. Conclusion: The examination in accordance with the question which “what is the role of nurse to prevent children from internet addiction” is concluded that there was not found any research about the roles of the nurses to protect children from internet addiction.